Long‐Term Treatment of Eosinophilic Esophagitis With Swallowed Topical Corticosteroids: Development and Evaluation of a Therapeutic Concept. (October 2017) - Greuter, Thomas; Bussmann, Christian; Safroneeva, Ekaterina; Schoepfer, Alain M; Biedermann, Luc; Vavricka, Stephan R; Straumann, Alex
Abstract : Objectives: Swallowed topical corticosteroids (STCs) are efficacious in inducing and presumably maintaining remission in patients with active eosinophilic esophagitis (EoE). Hitherto, it has not been evaluated whether long‐lasting remission can be achieved, and whether treatment can be stopped once patients have achieved this remission. Methods: Since 2007, EoE patients included into a large database at the Swiss EoE Clinics were put on STCs as induction/maintenance therapy. Disease activity was assessed on an annual basis. In patients who achieved long‐lasting (≥6 months) clinical, endoscopic, and histological (=deep) remission, treatment was stopped. Data on all patients treated using this therapeutic strategy were analyzed retrospectively. Results: Of the 351 patients, 33 (9.4%) who were treated with STCs achieved deep remission. Median age of remitters at disease onset was 32.6 years (interquartile range (IQR) 19.1–49.3), and diagnostic delay was 5.4 years (IQR 1.2–11.4). Deep remission was achieved after 89.0 weeks (IQR 64.6–173.8). Female gender was the only independent prognostic factor for achieving deep remission (odds ratio (OR) 2.518, 95% confidence interval (CI) 1.203–5.269). Overall, STCs were stopped after 104.7 weeks (IQR 65.5–176.6). No mucosal damage was observed upon histological examination. In 27 of the 33 remitters (81.8%), a clinical relapse occurred after a median of 22.4 weeks (95% CI 5.1–39.7). Six remitters (18.2%) did not experience a clinical relapse during a follow‐up of 35.1 weeks (IQR 18.3–44.9). Hence, a total of 1.7% (6/351) patients were able to discontinue STCs in the long term. Conclusions: Long‐term EoE treatment with STCs was well tolerated, but only a minority achieved deep remission. Female gender is the only prognostic factor for attainment of such remission. After treatment cessation, the majority experienced a clinical relapse.